PENANGANAN SENGKETA TATA USAHA NEGARA (TUN) YANG TIDAK TERMASUK KEPUTUSAN TATA USAHA NEGARA (KTUN) OLEH PERADILAN UMUM (PU) SETELAH PENERAPAN UNDANG-UNDANG NOMOR 9 TAHUN 2004 TENTANG PTUN - Misranto Misranto (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
The conflict management of State Administration (TUN) does not include the decision of State Administration (KTUN) by General Court afer the implementation of the regulation number 9 by the year of 2004 could be understood through three points: first, the conflict of State Administration (TUN) which does not include the decision of State Administration (KTUN) becomes General Court’s competence; second, the conflict of State Administration (TUN) which is out of question becomes General Court’s competence; third, the conflict of the decision of State Administration which becomes State Administration Court’s competence. With those three points in mind, the problem solution should be searched from the aspects of doctrine and the aspects of decision. The aspects of doctrine would be analyzed to broaden the vision in decision making, while the aspects of decision would be the jurisprudence of the judges in decision making. Not every decision of State Administration becomes the State Administration Court’s competence. There would be some decisions of State Administration become the General Courts competence. To deal with it, the State Administration Court’s competence need to be broaden so the institution would become independent. Besides, there would be some unsuitable understanding form the law so the confirmation of the understanding would be necessary.